SISTEM KENDALI KERETA OTOMATIS PADA KERETA REL LISTRIK VVVF - Liem Ek Bien, Liem Ek Bien; Kasim, Ishak; Hartanto, Hednry (Jurnal Teknik Elektro, 2006)
The most challenging issues in railway systems today is a driverless systems which includesmodern requirements for safety and reliability and also allows the basic improvement of theflow and effectivity of the operation including a comfort improvements for operators. Thesystems was known as Automatic Train Control (ATC) system. The ATC here is able to keepthe scheduled time and to optimize the train running with respect to minimum energyconsumption, also considerably simplify the driverâs work.Keywords: Automatic Train Control, Automatic Train Operations, Automatic TrainProtection.